The Association Between Vitamin C and Cancer: A Two-Sample Mendelian Randomization Study - Chen, Hanxiao; Du, Ze; Zhang, Yaoyao; Li, Mengling; Gao, Rui; Qin, Lang; Wang, Hongjing (Frontiers in Genetics, 2022)
In recent years, many studies have indicated that vitamin C might be negatively associated with the risk of cancer, but the actual relationship between vitamin C and cancer remains ambivalent. Therefore, we utilized a two-sample Mendelian randomization (MR) study to explore the causal associations of genetically predicted vitamin C with the risk of a variety of cancer. Single nucleotide polymorphisms (SNPs) associated with vitamin C at significance level of P < 5×10-8 and with low level of linkage disequilibrium (LD) (r2 < 0.01) were selected from a genome-wide association study (GWAS) meta-analysis of plasms concentration of vitamin C consisting of 52,018 individuals. GWAS outcome data were obtained from UK Biobank, FinnGen Biobank, and the datasets of corresponding consortia. In inverse-variance weight (IVW) method, our results did not support the causal association of genetically vitamin C with the risk of overall cancer and fourteen specific types of cancer types. Similar results were observed in sensitivity analyses where the weighted median and MR-Egger methods were adopted, and heterogeneity and pleiotropy were not observed in statistical models. Therefore, our study suggested that vitamin C was not causally associated with the risk of cancer. Further studies are warranted to discover the potential protective and therapeutic effect of vitamin C on cancer, as well as its underlying mechanisms.